Controlled and Automatic Processing in the Acceptability Judgment Task: An Eye‐Tracking Study. Issue 1 (26th October 2021) - Maie, Ryo; Godfroid, Aline
Abstract: We conducted an eye‐tracking study of the acceptability judgment task (AJT) by drawing on the dual process theory of controlled and automatic processing. We conceptually replicated the work of Godfroid et al. (2015) and then extended it in two respects: (a) we analyzed both late and early measures of eye movement to differentiate between the effect of time pressure on controlled and on automatic processes, and (b) we examined how the automaticity of participants' lexical processing moderated the effect of time pressure. Under timed and untimed conditions, 31 L1 and 40 L2 English speakers performed the AJT while their eye movements were recorded. Through statistical modeling of the eye‐tracking data, we demonstrated that (a) time pressure inhibits not only controlled processing but also automatic processing and (b) the time pressure effect is most pronounced for the late eye‐movement measures of L2 speakers with slow lexical decoding skills. We explain that time pressure may not work as theoretically predicted by L2 researchers (i.e., to suppress only controlled processes associated with explicit knowledge) and that its effect is not uniform across different L2 speakers. Abstract :